2009
DOI: 10.1111/j.1468-5906.2009.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Traditionalism Among Conservative Protestants: Does the Difference Make a Difference?

Abstract: Recent years have witnessed the resurgence of conservative Protestantism and its adherents' advocacy of gender traditionalism. Scholarship has traced conservative Protestant women's support for gender traditionalism to biblical inerrancy while linking conservative Protestant men's support for gender traditionalism to their denominational affiliation. Our study revisits this issue with more recent data, more sophisticated analytical techniques (structural equation modeling), and a refined measure of theological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 15 publications
(36 reference statements)
0
40
1
Order By: Relevance
“…For example, those Protestants that adhere to a more conservative theology may have quite different belief systems regarding fear of crime than rather liberal Protestants [34]. Relatedly, more in depth measures of religious beliefs could help more effectively elucidate differences in fear of crime, in a similar manner to recent research which has demonstrated differences in gender beliefs rooted in religious ideology [35].…”
Section: Discussionmentioning
confidence: 69%
“…For example, those Protestants that adhere to a more conservative theology may have quite different belief systems regarding fear of crime than rather liberal Protestants [34]. Relatedly, more in depth measures of religious beliefs could help more effectively elucidate differences in fear of crime, in a similar manner to recent research which has demonstrated differences in gender beliefs rooted in religious ideology [35].…”
Section: Discussionmentioning
confidence: 69%
“…For instance, theological conservatism and religious attendance predict gender essentialism but not beliefs related to separate spheres (Bartkowski and Xu 2010). Moreover, the social underpinnings of gender ideology sometimes work differently for religious men than for women (Bartkowski and Hempel 2009). Furthermore, qualitative research has revealed that ideological commitments to gender essentialism among religious adherents do not lead ineluctably to support for patriarchy or separate spheres (Bartkowski 2001;Mihelich and Storrs 2003).…”
Section: Latina/o Gender Ideology: Integrating Current Research With mentioning
confidence: 99%
“…This does not of itself explain why women should be more literalist than men, who could equally draw on literalist interpretations to uphold views that deny women access to ordination. However, Bartkowski & Hempel (2009), in a study of conservative Protestants in the United States that built on the work of Peek, Lowe and Williamson (1991), found that women who supported gender traditionalism tended to do so for theological reasons, whereas among men This study shows the value of using a summated-rating literalism scale within a single denomination that has varying attitudes towards the ordination of women. It highlights the way that literalism can vary in a predicable fashion between traditions in the same denomination, and also between different groups in the same tradition.…”
Section: Discussionmentioning
confidence: 83%
“…This correlation is not a simple one, and there is some evidence that the relationship between biblical literalism and sexism may vary between men and women, with women's views being driven by personal convictions and men's views being linked to group membership (Bartkowski and Hempel 2009;Peek et al 1991). Women are not necessarily less literal than men, and indeed may be more literal in some cases.…”
Section: Introductionmentioning
confidence: 99%